Community Relations sebagai Strategi Legitimasi Sosial: Analisis Konseptual Pembentukan Citra Perusahaan dalam Perspektif Public Relations - Selvi Andreana Fatikasari; Siti Munawaroh; Excel Sujanto; Pramudya Ibnu Subrata (CITACONOMIA : Economic and Business Studies, 2026)
The relationship between corporations and local communities has become an increasingly important issue in contemporary public relations practices, particularly for companies operating in resource-based industries. Community relations is widely recognized as a strategic communication approach that enables organizations to build sustainable relationships with surrounding communities while strengthening social legitimacy and public trust. This conceptual article aims to analyze the role of community relations in shaping corporate image from a public relations perspective. The study employs a descriptive qualitative approach commonly used in conceptual research, supported by a literature review of relevant theories on stakeholder management, corporate reputation, and social license to operate. The analysis indicates that effective community relations practices involve dialogic communication, community participation, and transparent engagement between organizations and local stakeholders. Such interactions allow companies to better understand community expectations and respond to social concerns surrounding their operations. Furthermore, the findings suggest that well-managed community relations can enhance social acceptance, strengthen organizational legitimacy, and contribute positively to the formation of corporate image. By integrating perspectives from stakeholder theory and public relations relationship management, this study proposes a conceptual framework explaining how community relations can influence corporate image through trust-building and community engagement processes. The study contributes to the development of public relations scholarship by emphasizing the strategic role of community relations in supporting organizational sustainability and reputation management